2010
DOI: 10.1371/journal.pgen.1001161
|View full text |Cite
|
Sign up to set email alerts
|

Gimap3 Regulates Tissue-Specific Mitochondrial DNA Segregation

Abstract: Mitochondrial DNA (mtDNA) sequence variants segregate in mutation and tissue-specific manners, but the mechanisms remain unknown. The segregation pattern of pathogenic mtDNA mutations is a major determinant of the onset and severity of disease. Using a heteroplasmic mouse model, we demonstrate that Gimap3, an outer mitochondrial membrane GTPase, is a critical regulator of this process in leukocytes. Gimap3 is important for T cell development and survival, suggesting that leukocyte survival may be a key factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 33 publications
3
62
0
1
Order By: Relevance
“…Previously we identified M. musculus allelic variants of Gimap3 that affect mtDNA segregation in hematopoietic tissues (Jokinen et al 2010). In the common lab mouse strains with a M. m. domesticus background, such as BALB/c, Gimap3 contains five exons and transcription produces an mRNA with two AUG codons as potential start codons for translation initiation ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we identified M. musculus allelic variants of Gimap3 that affect mtDNA segregation in hematopoietic tissues (Jokinen et al 2010). In the common lab mouse strains with a M. m. domesticus background, such as BALB/c, Gimap3 contains five exons and transcription produces an mRNA with two AUG codons as potential start codons for translation initiation ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the uORF has a greater Kozak consensus sequence around the AUG than that seen for the downstream reading frame of Gimap3 ( Figure 1B). Unless indicated otherwise, hereafter Gimap3 refers to the allele found among the common lab strains with a M. m. domesticus background that encodes the 301-aminoacid protein (Jokinen et al 2010). In contrast, the subspecies M. m. castaneus has a mutation in the splice acceptor site of exon 4 causing a splicing defect leading to the absence of exon 4 from the CAST Gimap3 mRNA ( Figure 1A) (Jokinen et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two different normal mtDNA were found to be actively segregated for during the animal lifespan, in a non-random fashion as one genotype was favored in kidney and liver while the other one was favored in blood and spleen [35]. Using linkage analysis and crosses with distantly related mouse species, Battersby et al found three potential loci controlling the tissular segregation [36] and, more recently, identified GIMAP3 as a gene controlling active mtDNA segregation in blood [37]. How this gene can influence the fate of a normal mtDNA still remains an open question.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%